Juridical Review of The Crime of Theft Committed by Minors - Fernando, Youngky (The International Journal of Education Management and Sociology, 2022)
The aim of this research is to understand the criminal act of theft committed by children, and to analyze the judge's considerations in handing down decisions in cases of criminal acts of theft of minors (Decision Number 10K/Pid.Sus/2018/PN.Tng). This research method uses the type of research carried out in this thesis is qualitative. Meanwhile, this research is included in the category of normative or doctrinal research. The research approach used in this research is normative juridical. The data collection method used in this research is document study. Also, data collection techniques are document study methods and library research methods. The data obtained will be processed using qualitative analysis. The results of the research show that the judge's considerations for the child are in accordance with the provisions of the juvenile justice system, in some of the judge's considerations the child was sentenced to only a third of the full sentence demanded by the public prosecutor, the child should have been sentenced to 10 months but at the judge's discretion the child was sentenced to only 6 months. As well as the qualifications of criminal acts of theft with aggravation committed by children from the perspective of criminal law.